DFT-based molecular conformational analysis of a diarylethylene cyano-derivative - Abulyaissova, L. K. (Journal of Structural Chemistry, 2019)
Structural stability and conformational behavior of trans-4,4′-methoxycyanostilbene are studied theoretically within the method of density functional theory using the B3LYP functional and 6-31G(d) and cc-pVDZ split-valence basis sets. According to quantum chemical calculations performed for the molecule in its ground state, two possible conformations of the molecule differ in energies so that the configuration with triple conjugation (p,π-, π,π-, and direct polar conjugation of substituents) is energetically preferable. First- and second-order saddle points are found by scanning the three-dimensional potential energy surface. Vibrational analysis is used to find stationary points.
Keywords: diarylethylene cyano-derivative; stilbene; conformational analysis; potential energy surface; density functional theory